A global review of vessel wave effects on land-water interfaces: collaborative baselining of issues, management strategies and future challenges - Melling, Gregor; Holzwarth, Ingrid; Dempwolff, León-Carlos; Windt, Christian; Goseberg, Nils (Journal of Coastal and Hydraulic Structures, 2025)
Waterborne vessels of all types generate waves as a result of their movement through and displacement of water. These surface disturbances spread toward the boundaries of waterways, where they interact with both natural and built environments, often with adverse effects. The magnitude and frequency of impacts related to vessel waves are becoming increasingly evident in estuarine and coastal waterways worldwide. As an outcome of an international workshop, drawing on the collective expertise of academics, practitioners, and policymakers from various disciplines, this overview synthesizes the current 'state of play' regarding the varied effects of vessel waves in sheltered water bodies, associated use conflicts, and potential mitigation strategies. These insights are presented within the context of existing literature and include references to illustrative case studies. While there is broad recognition of the need to manage the impact of vessel waves on both built and natural environments, challenges such as gaps in process understanding, regulatory limitations, political complacency, and economic realities of global seaborne trade can impede effective mitigation of vessel wave effects on land-water interfaces. With an anticipated increase in waterborne transportation and recreational boating on one hand and the need to reduce adverse effects of intense waterway use on the other, vessel waves are a prominent topic, underscoring the future requirements for improved process understanding, monitoring, data sharing and the importance of holistic management of vessel-related impacts in waterways.